COMPARISON OF MEAN DASH SCORE AFTER CLOSE REDUCTION AND EXTERNAL FIXATION VERSUS OPEN REDUCTION INTERNAL FIXATION (ORIF) WITH PLATING FOR TREATING INTRA-ARTICULAR FRACTURE OF DISTAL RADIUS - Zulﬁqar Ahmad; Mueed Ahmad; Hayyan Ahmad (Journal of University Medical & Dental College, 2018)
ABSTRACT: OBJECTIVE: To compare the mean DASH score after close reduction and external ﬁxation versus ORIF with plating for treating intra-articular fracture of distal radius. MATERIALS & METHODS: Total 60 subjects having fracture of intra-articular distal radius having age from 20-60 years either male or female were selected for present study. Patients with rheumatoid arthritis, neurovascular injury, diabetes mellitus, chronic liver disease, chronic renal failure, chronic steroid use were excluded. Two equal study groups A and B were made by randomization. In group A patients, ORIF with plating was done while in group B, external ﬁxation was done. At the end of 6 months of surgery, DASH score was evaluated in both groups. RESULTS: Average age in study group A & B was 31.90 ± 7.86 years and 33.53 ± 8.49 years respectively. Total 41 (68.33%) patients were male and 19 (31.67%) patients were female. The mean duration of fracture in group A was 34.47 ± 17.67 hours and in group B was 35.10 ± 17.33 hours. Mean DASH score in Group A (ORIF with plating) was 28.04 ± 10.47 while in Group B (external ﬁxation) was 52.17 ± 8.73 (p-value<0.0001). CONCLUSION: Findings of present study showing that mean DASH score is less after ORIF with plating as compared to external ﬁxation technique for treating intra-articular fracture of distal radius.